Management of Herpangina - Maharani Laillyza Apriasari; Juliyatin Putri Utami (Denta Journal Kedokteran Gigi, 2020)
Background: Herpangina is an acute infectious disease with self-limiting properties. While herpangina may heal without any treatment, it may be followed by various complications such as meningitis, encephalitis, cardiomyopathy, or even death. In 2018, there was a 10.07% prevalence rate of viral infection in Banjarmasin city, South Kalimantan. One of which was herpangina. Objective: To elucidate the management of herpangina. Case: Young female patient, 11 years old, complained of multiple ulcerations on the posterior side of her mouth with excruciating pain when swallowing. Ulceration had appeared for three days which was initially commenced by fever and cough. Case Management: The patient was prescribed methisoprinol syrup 250 mg four times a day, ibuprofen syrup 250 mg four times a day, mouthwash containing aloe vera extract to be applied thrice daily, and explicit instruction for bed rest. Conclusion: Dental practitioners must differentiate herpangina from other differential diagnoses thus enabling the acquirement of final diagnosis through clinical examination. This will significantly assist dental practitioners to provide precise clinical therapy for the patient with herpangina.